Grafting, agrochemicals, and oxidative enzymes as factor for plant biotic resistance - Monteiro, Gean Charles [UNESP]; Goto, Rumy [UNESP]; Minatel, Igor Otavio; de Sousa da Silva, Edvar; da Silva, Ewerton Gasparetto; Vianello, Fabio; Lima, Giuseppina Pace Pereira [UNESP] (Springer Nature, 2019)
Grafting has been practiced to overcome yield problems associated to soil-borne diseases or declines in production. Usually this agricultural method involves the choice of better stock and scion species, procedures to improve the graft union and subsequent healing, and acclimation of the grafted plant to soil. Similarly, to agrochemicals used in vegetable production, this method may induce changes in oxidative enzymes production by plants and consequently provide a higher resistance to biotic stresses. Microorganisms are one of the major concerns in agricultural practices, mainly by its increasing resistance to chemical products regularly applied in cultures. Nevertheless, the association of grafting methods to agrochemicals usage is a wide field of study that should be better interpreted by considering not only the resulting production, but their interactions and consequences in the plant metabolism. The purpose of this chapter is to review the resistance induced in plants by grafting methods or agrochemicals. In addition, the role of oxidative enzymes produced for resistance mechanisms is discussed.
Keywords: Antioxidant activity; Phenolic compounds; Polyamines; Reactive oxygen species; Salicylic acid